Effective Teaching of the Online Class Learning in Professional Subjects in Hospitality Management: Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Bachelor of Science in Hospitality Management course professionally prepares and equips students with skills to perform daily tasks in food production, accommodations, and food-beverage service operations. The course trains them to be highly qualified hospitality and tourism practitioners who cater to their constituents and those in professional fields while sustaining the best ethical and moral standards and showcasing the best skills proficiency. Online classes are an environment created through a learning management system that allows students and teachers to connect synchronously or asynchronously, with interaction between teachers and students generally separated by location. Teaching through online classes it is a combination of synchronously and asynchronously. In synchronous, the professor and the students meet through G-meet or Zoom. In that way, they can discuss the lesson face-to-face. Asynchronously, tasks like activities, quizzes, and exams can be delivered to the professor anytime. This study aims to determine if online learning is productive for students and whether it allows students and professors to connect more confidently. The procedure of obtaining Likert scale survey questionnaire data is referred to as a quantitative design type of research under the descriptive approach in this study. The subject will consist of 97 respondents ranging from first-year to fourth-year BSHM students. The volunteers were chosen based on their profile, which will provide the researchers with the required information. The researchers will survey using Google Forms and a Likert scale to see if online classes are effective or ineffective in teaching professional subjects. We discovered that even without equipment and actual activities, it's not a hindrance to studying BSHM professional subjects. Based on the findings from the effectiveness of the online classes in professional subjects in teachers' mastery, the overall weighted mean is 3.54 or effective. This implies that the respondents believe that the teacher's mastery of the subject matter greatly affects the online learning modality. From students' internet connectivity and participation in LMS and virtual classes, the overall weighted mean is 3.48 and verbally interpreted as effective. This implies that the student's learning is effective when a sufficient and reliable internet connection enables them to participate in online classes and access the LMS. In students' focus on enhancing skills in performing in production, the overall weighted mean is 3.47, and a verbal interpretation is effective. This implies that enhancing the skills of students' BSHM can improve production performance. Lastly, the strategies for improving learning in BSHM professional subjects, the overall weighted mean is 3.64 and is verbally interpreted as effective. This implies that the strategies for improving learning hospitality management subjects are effective. Giving quizzes and exams, tracking students' progress, and performing activities help the professor know if their mastery of the subject matter is effective. The G-meet discussion and instructional materials can encourage students to study and understand the lesson. The students' learning is effective when a sufficient and reliable internet connection enables them to participate in online classes and access the LMS. By computer compliance, the students can easily participate and comply with activities. Not everyone has a good relationship in their house, and one of the students' struggles is their mental and physical health, which can hinder them from studying. Understanding them may help them have the courage to study and focus on themselves to practice their skills in real-time activities and have quality skills. Having a visual distraction is one of the struggles in learning virtually, but I can avoid it and collaborate with value and skills in performing in production. Using resourceful websites, easily passing documents through Gmail, and flexing lesson plans are the strategies for improving students' learning of BSHM subjects. Providing ongoing feedback and seminars via webinars also helps students and professors know if they are effective in learning hospitality management subjects.
Keywords: Online Teaching; Professional Subjects; Bachelor of Science Hospitality Management